Pengaruh Pemahaman Kebijakan Perpajakan, Undang-Undang Perpajakan dan Administrasi Perpajakan terhadap Penerapan Perencanaan Pajak - Hetiati Hetiati; Memen Kustiawan; Fitriana Fitriana (Jurnal Syntax Transformation, 2021)
This research was conducted in KPP Pratama Cibeunying with the number of respondents as many as 84 corporate taxpayers with descriptive research methods and verifikative quantitative approach. Primary data collection using questionnaires. The purpose of this research is to find out the influence of understanding tax policy, tax law, and tax administration on the application of tax planning in KPP Pratama Cibeunying. Technical analysis of this study uses multiple linear regression analysis. The results in this study show that variable understanding of tax policy, tax law, and tax administration has an effect on the implementation of tax planning both partially and simultaneously.